Pemberdayaan dan Pemasaran Produk UMKM melalui Kegiatan Bazar di Desa Ciamaragas Kabupaten Ciamis - Andifa Dwi Fani; Dede Husni Mubarok; Aiddatul Fitroh; Gea Lisdiani; Dika Hadisurya (Khidmat, 2022)
This community service article focuses on efforts to empower MSMEs in Cimaragas Village through bazaar activities. Cimaragas Village is one of the villages that has business potential that can be developed. In this area, there are various types of food processing industries to household goods processing industries. However, the majority of MSMEs have the biggest obstacle, namely in entrepreneurship, they still lack access to product marketing, so it is difficult in promoting their production goods. This research uses qualitative research methods with descriptive research types. The results of this service are an increase in product sales through the UMKM bazaar stall, better recognition of MSME products in Cimaragas village and the community can promote so that the market share becomes wider.